The phototactic rhythm of pests for the Solar Insecticidal Lamp: A review - Yao, Heyang; Shu, Lei; Yang, Fan; Jin, Yinghao; Yang, Yuli (Frontiers in Plant Science, 2023)
Pest management has been a great challenge since the beginning of human agricultural activities. Since the 1930s, chemical pesticide control has been a major control technology that can solve some of the pest problems in agricultural production. Still, it is harmful to food safety and the ecological environment. Meanwhile, the extensive use of chemical pesticides may lead to the rapid development of pest resistance. Because of the advantages of low cost, eco-friendly advantage, and low side effects, Solar Insecticidal Lamp (SIL) as the main physical control technology has been widely used for pest management in agricultural production in China. Owing to the phototaxis of pests, they have a phototropic rhythm during the nighttime. We can adjust the SIL insecticidal time according to the phototropic rhythm of pests. The purpose of this paper is to provide a comprehensive review of the pest phototactic rhythm in a selection of 24 pest species. It is the first comprehensive survey on the phototactic rhythm of pests and the time segments of this survey are accurate to the hour. The phototactic rhythm of pests are investigated in two different varieties of crops: 1) food crops and 2) economic crops. We also discuss and analyze the various factors (e.g., meteorological conditions, insecticidal devices, physiological states and others) that affect the changing phototactic rhythm of pests. Finally, we highlight some open research challenge issues and future directions.